2020
DOI: 10.1530/eje-20-0394
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: Rationale and current evidence for testosterone therapy in the management of obesity and its complications

Abstract: Overt hypogonadism in men adversely affects body composition and metabolic health, which generally improve upon testosterone (T) therapy. As obese men often display lower serum T levels, in particular when they present with the metabolic syndrome (MetS) or type 2 diabetes (T2DM), there have been claims that androgen therapy prevents or reverses obesity and improves metabolic health. This has contributed to the increase of T prescriptions during the past two decades. In this narrative review, based on findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 132 publications
(213 reference statements)
1
8
0
4
Order By: Relevance
“…We therefore suggest prescribing the same adult starting dose of testosterone to men with PWS and personalising the maintenance dose as in normal men with hypogonadism. In some men with visceral obesity, it might be better to monitor free testosterone levels during treatment for tailoring treatment [36]. In adolescents and women who are potentially fertile (e.g., inhibin B levels above 20 pg/mL), contraceptive measures should be taken; we prescribe an oral contraceptive pill in these cases.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore suggest prescribing the same adult starting dose of testosterone to men with PWS and personalising the maintenance dose as in normal men with hypogonadism. In some men with visceral obesity, it might be better to monitor free testosterone levels during treatment for tailoring treatment [36]. In adolescents and women who are potentially fertile (e.g., inhibin B levels above 20 pg/mL), contraceptive measures should be taken; we prescribe an oral contraceptive pill in these cases.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In obese men, sex hormone-binding globulin (SHBG) and resultant testosterone levels can be low. Therefore, it is recommended to also measure free testosterone levels and SHBG in order to decide whether free testosterone should be measured to monitor and tailor therapy [36]. Haemoglobin levels should also be monitored as there is a risk of erythrocytosis when testosterone levels are too high.…”
Section: Treatment 231 Supplementing Gonadal Hormones In Normal Mamentioning
confidence: 99%
“…Accordingly, several cross-sectional and longitudinal studies have reported an inverse correlation between serum testosterone level and indices of obesity and metabolic risk [reviewed in ref. 51]. In turn, interventional studies have shown a beneficial effect of testosterone replacement therapy on BMI, adipose tissue distribution, and body composition in hypogonadal men [14].…”
Section: Metabolic Consequences Of Hypogonadismmentioning
confidence: 99%
“…Кроме того, на фоне статей, подтверждающих эффективность ТЗТ, есть убедительные работы, которые акцентируют внимание на негативных сторонах ТЗТ и обосновывают свою позицию [21,22]. Прежде всего важно модифицировать образ жизни и мотивировать пациента к снижению объема жировой ткани, так как без этих важнейших действий можно не добиться никакого эффекта даже при использовании максимально успешных препаратов [23]. Тестостерон не является конечной точкой в стероидогенезе.…”
Section: взаимосвязь тестостерона и эстрадиолаunclassified